2022
DOI: 10.1186/s40168-022-01283-2
|View full text |Cite
|
Sign up to set email alerts
|

Aging gut microbiota of wild macaques are equally diverse, less stable, but progressively personalized

Abstract: Background Pronounced heterogeneity of age trajectories has been identified as a hallmark of the gut microbiota in humans and has been explained by marked changes in lifestyle and health condition. Comparatively, age-related personalization of microbiota is understudied in natural systems limiting our comprehension of patterns observed in humans from ecological and evolutionary perspectives. Results Here, we tested age-related changes in the divers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 109 publications
0
12
0
Order By: Relevance
“…Some of these studies show a large effect of individual identity on the microbiome over a period of two months [1], 1.5 years [2], 2 years [3] or 8 years [4]. However, in two of these cases [2,4], the effects were time dependent. Other longitudinal studies of the microbiome where individuals were repeatedly sampled over long periods of time include individual identity as a random effect in their statistical models to control for individual variation, but do not directly test what proportion of the variation is explained by identity [5][6][7].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some of these studies show a large effect of individual identity on the microbiome over a period of two months [1], 1.5 years [2], 2 years [3] or 8 years [4]. However, in two of these cases [2,4], the effects were time dependent. Other longitudinal studies of the microbiome where individuals were repeatedly sampled over long periods of time include individual identity as a random effect in their statistical models to control for individual variation, but do not directly test what proportion of the variation is explained by identity [5][6][7].…”
mentioning
confidence: 99%
“…The individuality of the microbiome has been examined previously over various timescales, but primarily using comparisons of within versus between individual similarity. Some of these studies show a large effect of individual identity on the microbiome over a period of two months [1], 1.5 years [2], 2 years [3] or 8 years [4]. However, in two of these cases [2,4], the effects were time dependent.…”
mentioning
confidence: 99%
“…Thus, we also tested for greater intra-and inter-individual variation amongst samples taken in older age groups. Such heterogeneity has previously been identi ed in humans [15,46] and wild macaques (Macaca assamensis) [30]. We extended this research by also testing whether GM variation is greatest during the terminal year due to greater instability.…”
Section: Introductionmentioning
confidence: 63%
“…However, no clear consensus has emerged from this research. Whilst some studies have reported shifts in GM composition [28,29] and greater GM heterogeneity with increasing age [30], others have found that GM dynamics and overall composition remain largely invariable throughout adulthood [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Although age‐dependent changes to gut microbial composition are known from a variety of wildlife species (Barbosa et al, 2016; Risely et al, 2022; Sadoughi et al, 2022), it remains unknown how changes in composition relate to changes in rhythms. Exploiting systems with high survival rates that have previously been used to model senescence and demography, such as seabirds (Fay et al, 2018; Patrick & Weimerskirch, 2015) or long‐lived mammals (Robinson et al, 2012), may help clarify this question.…”
Section: Relevance Of Microbial Oscillations To Outstanding Questions...mentioning
confidence: 99%